Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
28 ^7 : 4 ^ 7 =(28:4)^7=7^7
5 ^ 6* 7 ^ 6 =(5*7)^6=35^7
8^9 * 8^7 =8^16
5^0 - 5^3 =1-125= -124
2 ^3 + 4^3 =8+64=72
(6^7) ^3 =6^21
15^10 : 15^2 =15^8
3 ^2 + 11^2 =9+121=130
Odpowiedź i szczegółowe wyjaśnienie:
[tex]\dfrac{28^7}{4^7} =\dfrac{(7\cdot4)^7}{4^7}=\dfrac{7^7\cdot4^7}{4^7}=7^7\\\\5^6\cdot7^6 =(5\cdot7)^6=35^6\\\\8^9\cdot8^7=8^{9+7}=8^{16}\\\\5^0 - 5^3 =1-125=-124\\\\2^3+ 4^3 =8+64=72\\\\(6^7)^3 =6^{7\cdot3}=6^{21}\\\\15^{10} : 15^2=15^{10-2}=15^8\\\\3^2 + 11^2 =9+121=130[/tex]
Wykorzystano podstawowe własności potęgowania:
[tex]a^n\cdot a^m=a^{n+m}\\\\a^n:a^m=a^{n-m}\\\\(a^n)^m=a^{n\cdot m}\\\\(ab)^n=a^n\cdot b^n[/tex]